2020
DOI: 10.3168/jds.2020-18193
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of risk factors for bovine viral diarrhea virus in cattle herds: A systematic search and meta-analysis of observational studies

Abstract: These pooled values must be interpreted with care, as there was a high level of heterogeneity between studies. However, they do give an indication of the importance of the most frequently studied risk factors and can therefore assist in the development, evaluation, and optimization of BVDV control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 85 publications
2
17
0
Order By: Relevance
“…In this study, we showed that herds with a free or unsuspected status for the evaluated infections had lower mortality rates in calves and cows than herds with an unknown status. Infectious diseases are risk factors for mortality and culling as previously reported for BVD ( 81 , 82 ), salmonellosis ( 83 , 84 ), and paratuberculosis ( 85 88 ). Nevertheless, the effect estimates presented in this study are likely to be underestimated, given that some of the herds with an unknown status will also be free from infection.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, we showed that herds with a free or unsuspected status for the evaluated infections had lower mortality rates in calves and cows than herds with an unknown status. Infectious diseases are risk factors for mortality and culling as previously reported for BVD ( 81 , 82 ), salmonellosis ( 83 , 84 ), and paratuberculosis ( 85 88 ). Nevertheless, the effect estimates presented in this study are likely to be underestimated, given that some of the herds with an unknown status will also be free from infection.…”
Section: Discussionmentioning
confidence: 60%
“…As testing is required for all new-born calves, this is a useful proxy for the size of breeding herds within NI. This association with herd size is well-recognised (19) and probably reflects an association with known infection risks such as animal movements, number of neighbour contacts and farm visitors. An earlier analysis of spatial and herd-level risk factors during the first year of the compulsory programme revealed BVD "hotspot" areas and showed that previous positive status, herd size and the number of positive neighbours within 4 km were positively associated with infection (20).…”
Section: Discussionmentioning
confidence: 86%
“…Given the amount of data available, future models developed to compare outputs of various CPs could focus on the usage of nearly any data describing cattle demographics and cattle purchase data for risk of introduction of disease (16). However, although the introduction of cattle into a herd has been reported as an important risk factor for JD, IBR, and BVD in several studies (33)(34)(35), other risk factors, such as participation in shows, grazing, and calving pen systems, are also described as important for estimating freedom from infection (33). Our results show that very few countries in Europe have access to these data on a national or regional level.…”
Section: The Availability Of Data For Probability Of Freedom From Disease Estimatesmentioning
confidence: 99%